Śāntideva's Bodhicaryāvatāra in Translation: A Century of Interpretation of a Sanskrit Mahāyāna Text. (2nd November 2015) - Nelson, Barbara
Abstract : Many translations of Śāntideva's Bodhicaryāvatāra, a Sanskrit Mahāyāna Buddhist text of seventh/eighth‐century India, have been published since 1892. Śāntideva's Bodhicaryāvatāra is one of the few Indian Mahāyāna Buddhist texts available in Sanskrit and it was influential in Tibetan Buddhist schools. This article explores how translation of the Bodhicaryāvatāra is no longer the preserve of scholars but has moved to being carried out by Buddhist practitioners influenced by Tibetan schools of Buddhism. It shows how translators' motives for translating the text have reflected changing attitudes to Buddhism and its texts. Śāntideva's Bodhicaryāvatāra has been translated as a source of information, a literary work, an inspirational work and, with the rise of Western interest in Tibetan Buddhism in the late twentieth century, as a vehicle for the transmission of Buddhist teachings. Nevertheless, further scholarly investigation of the Sanskrit text of the Bodhicaryāvatāra remains to be done.